2021
DOI: 10.3390/nu14010038
|View full text |Cite
|
Sign up to set email alerts
|

Association of Household Income Level with Vitamin and Mineral Intake

Abstract: Appropriate nutrient intake is essential for maintaining health and resisting disease. The current study investigated the association between household income quintile and nutrient intake using data from KNHANES 2019. A total of 5088 South Korean adults were analyzed. The estimated average requirement cut-point method, extended to handle participants with intakes higher than the tolerable upper level, was utilized to determine the need for dietary modification. The suitability of overall vitamin, overall miner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…Because the data do not include salting at the table, more salting by men increases the difference (below). Intriguingly, could it derive from gender specific dietary choices and differences in natriuresis, microbiota, and nutrient metabolism [ 142 , 143 , 144 , 145 ]? Clearly, the sex difference in intake of sodium, its causes, mechanisms, and implications, require further investigation.…”
Section: Sex Differences In Dietary Sodium Intakementioning
confidence: 99%
“…Because the data do not include salting at the table, more salting by men increases the difference (below). Intriguingly, could it derive from gender specific dietary choices and differences in natriuresis, microbiota, and nutrient metabolism [ 142 , 143 , 144 , 145 ]? Clearly, the sex difference in intake of sodium, its causes, mechanisms, and implications, require further investigation.…”
Section: Sex Differences In Dietary Sodium Intakementioning
confidence: 99%
“…Students with higher living expenses usually come from affluent families. Studies have shown that family income is significantly related to nutritional intake [62]. Affluent individuals were more likely to adopt a high-quality diet and realize the importance of balanced nutrition to maintain health [63].…”
Section: Discussionmentioning
confidence: 99%